FORMATION OF THE EMPIRICAL COMPONENT SPIRITUALITY OF FUTURE TEACHERS BY MEANS TRAINING TASKS (Pedagogy of Higher and Secondary Education, 2007)
In this article author examines system of training's tasks which favour the forming of empirical component of future teacher's spirituality.